2021
DOI: 10.1002/sys.21591
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing model‐based systems engineering, modularity, and software container concepts to manage obsolescence

Abstract: Costs to replace obsolete parts are estimated to exceed $10 billion annually for military expenditures. 1 Other industries experience high costs related to obsolete parts as well. [2][3][4][5] Synergies between Model-Based Systems Engineering (MBSE) and modular design concepts should be leveraged to reduce those costs early in the design process. To date, obsolescence management, MBSE, and modularity have been studied, advanced, and presented in a mostly disjunct manner. Consequently, work to synergize these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(91 reference statements)
0
12
0
Order By: Relevance
“…In addition to this, attention must be paid to ensure that there is a common knowledge base from which the different architectures are derived. For this, systems engineering can provide useful insights and tools to more accurately expose and map these linkages (Walden et al, 2015;Morgan et al, 2021). Additionally, there is a need to identify and research module drivers at discipline level and linkages between different disciplin-specific components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, attention must be paid to ensure that there is a common knowledge base from which the different architectures are derived. For this, systems engineering can provide useful insights and tools to more accurately expose and map these linkages (Walden et al, 2015;Morgan et al, 2021). Additionally, there is a need to identify and research module drivers at discipline level and linkages between different disciplin-specific components.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, a further literature review on discipline-specific modularization was conducted. As a result, various sources, such as Morgan et al (2021), Campusano et al (2021) or Liu et al (2021), prove that modular design is also considered in software engineering, mentioned here as a representative of other development disciplines, due to limitations of this paper. Thus, it can be concluded that there is at least a multi-disciplinary modular design in the conceptualization of products.…”
Section: Research Backgroundmentioning
confidence: 99%
“…For all of these historical projects, only reactive obsolescence management strategies were employed. Reactive actions seek to resolve an obsolescence problem once obsolescence has occurred and impacts the system 19 . In other words, reactive obsolescence management only generally occurs once the repeated failure of an obsolescent component is causing system downtime, and lost revenue.…”
Section: Methodsmentioning
confidence: 99%
“…Reactive actions seek to resolve an obsolescence problem once obsolescence has occurred and impacts the system. 19 In other words, reactive obsolescence management only generally occurs once the repeated failure of an obsolescent component is causing system downtime, and lost revenue. The upgrade from an obsolescent component to a more modern component could therefore be justified based on economics.…”
Section: Survey Of Obsolescence At Industrial Process Sitesmentioning
confidence: 99%
“…If system definition ambiguities can hardly be measured, its decrease can be measured. The adoption of our method can result in mastering of current expenses on concept exploration, direct generation of user manual automatically generated from the validation datasheet, maybe even obsolescence management, following [22] adding multi physical dimensions to their claims.…”
Section: Theoretical Proposition: Optimization Processmentioning
confidence: 99%